Small island economies in the new international environment - Samuel, Wendell A. (1999)
Examines the situation of small developing states in the new international environment and provides some evidence on the adverse international transfer of income. Outlines briefly, the main elements in the New International Economic Order developed in the 1970s. Dicusses how the trade and related issues have been resolved in the current environment under the aegis of the World Trade Organization. Notes how the countries of the Organization of the Eastern Caribbean States (OECS) have fared in the new environment and the strategic policy responses. Discusses some implications of the developments in the new world order and the policy response of developing countries.